Effect of Large-Scale Mining Drainage on Groundwater Hydrogeochemical Evolution in Semi-Arid and Arid Regions - Luo, Ankun; Wang, Guangcai; Dong, Shuning; Wang, Hao; Shi, Zheming; Ji, Zhongkui; Xue, Jiankun (Frontiers in Environmental Science, 2022)
Groundwater in coal mining areas will be significantly affected by natural processes and human activities. However, the impacts of large-scale mining drainage on groundwater hydrochemistry are unclear in the semi-arid and arid coalfield in Northwest China. Especially for shallow buried areas, the spontaneous combustion of coal seam outcrops forms burnt rock that is rich in fractures. Being a strong water yield aquifer after receiving recharge, burnt rock has become a potential source of mine water inrush hazards. Therefore, drainage from this aquifer is necessary to eliminate potential hazards, which also leads to deterioration of the local ecological diversity and sustainability. The hydrogeochemical method is an effective way to study the source and evolution of groundwater in mining areas, and determine the long-term cumulative effect of mining and drainage on the hydrogeochemical evolution of burnt rock areas. It is, however, still poorly understood. In this study, we employed the hydrochemical and isotope (2H, 3H, 18O) to investigate the long-term effects of drainage on the hydrogeochemical evolution in the coalfield of southern Xinjiang, China. The results showed that the hydrochemical environment became more complex as the effect of recharge of different tritium-based groundwater age in multiple-layered aquifers system and lead to the changes of concentration of the chemical components. Before large-scale mining drainage, groundwater flowed from the west to the east and finally discharged into the Kuqa river. The major water-rock interactions that occurred were the dissolution of halite, carbonate and gypsum dissolution, cation exchange and dedolomitisation. After large-scale and long-term mining drainage from the burnt rock aquifer, the groundwater flow field had changed, and the Kuqa river turned to recharge into the burn rock aquifer, the hydrochemical evolution also changed from water-rock interaction to mixture. This was caused by the significant decline in groundwater level and changes in groundwater circulation in the mining area, which further led to the loss of valuable surface water resources in this arid area. Based on the characteristics and recharge conditions of burnt rock, we suggest that grouting can effectively cut off the hydraulic connection between the river and burnt rock, and thus protect water resources.